A comparison of the chemical compositions and nutrient values of the sanim and srithong varieties of the farmed golden apple snails (Gastropoda; Ampullariidae; Pomacea canaliculata) - Tanyamon Petcharat; Thanasak Sae‐leaw; Soottawat Benjakul; Sylvia Indriani; Jaksuma Pongsetkul; Tran Hong Quan; Ali Muhammed Moula Ali; Suthasinee Yarnpakdee; Supatra Karnjanapratum (Future Foods, 2024)
The comparison of the Sanim (SN) and Srithong (ST) varieties of the farmed apple snail Pomacea canaliculata as an alternative protein source has shown that ST contained more hydroxyproline and possessed a greater firmness than SN. Nevertheless, both varieties yielded similar protein contents of 20.90–23.07 % and exhibited similar texture, color, cooking yields and cooking losses after cooking. Good palatability with high liking score was obtained from both snail meat samples, particularly color, texture, and overall attributes. Snail meats possessed good nutritive value with an amount of protein and low fat content, whereas SN contained higher protein and total energy(P < 0.05). Other nutritionally useful chemicals (such as calcium, sodium, iron, vitamins B1 and B2) are present. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) results discovered that myosin heavy chain, paramyosin, and actin were the prevalent protein components. Differences in nitrogen content distribution were observed between SN and ST, in which alkaline-soluble protein was the major fraction. Amino acid composition and fatty acid content varied regarding snail varieties with a large amount of essential amino acids and good source of MUFA and PUFA. Therefore, both farmed SN and ST snails could be an effective alternative protein source with a significant amount of nutritive value.
Keywords: Meat and Animal Product Quality; Mollusks and Parasites Studies; Agriculture Sustainability and Environmental Impact